Do hostels play a role in pleasing Millennial travellers? The Portuguese case - Veríssimo, Medéia (2021)
Abstract Purpose – The purpose of this paper is to identify the best hostel practices and trends, and to evaluate and discuss how they are keeping up with the present demand created by the Millennials market. Design/methodology/approach – Methodological approach is based on two complementary qualitative methods: ethnographic participant observation and netnography. Portuguese hostels are the target of this study, as they are considered some of the best in the world. First, a fieldwork was conducted in three top-rated hostels in Lisbon, aiming to immerse in hostel’s environment. Then, 300 online reviews were analysed to identify what customers value the most in those services. Data interpretation was done through a content analysis crossing supply-demand perspectives. Findings – Results indicate that, while staying in a hostel, the Millennials want to: meet people, engage in activities and events, have local experiences, feel comfortable/at home, get good value for money and enjoy the convenience. In return, hostels play an important role in hospitality industry by pleasing the Millennials, by offering: central location, an interactive atmosphere, functional facilities, well-planned design and decoration, a set of activities and events and personal treatment. Originality/value – This paper is one of the few to describe Millennials’ travel behaviour towards hostels’ services.